Quantitative study of developmental biology confirms Dickinsonia as a metazoan - Hoekzema, RS; Brasier, MD; Dunn, FS; Liu, AG (Royal Society, 2017)
The late Ediacaran soft-bodied macroorganism Dickinsonia (age range approx. 560–550 Ma) has often been interpreted as an early animal, and is increasingly invoked in debate on the evolutionary assembly of eumetazoan body plans. However, conclusive positive evidence in support of such a phylogenetic affinity has not been forthcoming. Here we subject a collection of Dickinsonia specimens interpreted to represent multiple ontogenetic stages to a novel, quantitative method for studying growth and development in organisms with an iterative body plan. Our study demonstrates that Dickinsonia grew via pre-terminal ‘deltoidal’ insertion and inflation of constructional units, followed by a later inflation-dominated phase of growth. This growth model is contrary to the widely held assumption that Dickinsonia grew via terminal addition of units at the end of the organism bearing the smallest units. When considered alongside morphological and behavioural attributes, our developmental data phylogenetically constrain Dickinsonia to the Metazoa, specifically the Eumetazoa plus Placozoa total group. Our findings have implications for the use of Dickinsonia in developmental debates surrounding the metazoan acquisition of axis specification and metamerism.